Photodestruction of Chloroplast Ultrastructure by Red Light: Location of Chlorophyll - Walne, Patricia L. (1970)
A lethal dose (1 Mrad) of gamma rays was given to wheat leaf tissue to restrict migration of the energy of red light photoexcitation to the photosynthetic pigment system. This dose of gamma radiation had no apparent effect on chloroplast ultrastructure in tissue that received no illumination. Subsequent illumination with red light, used to induce chlorophyll-sensitized photodestruction of ultrastructure, permitted inferences about the location of chlorophyll within the chloroplast. The red light produced extensive disruption in chloroplasts but not in any other cellular organelles. The sequence of events in this photodestruction was different from that which occurs when chloroplasts are destroyed by methods that do not involve illumination. The red light caused peculiar abnormalities only in the internal lamellar system of the chloroplast and not in the envelope or any other regions. These findings support other studies which suggest that chlorophyll is located exclusively in grana and stroma lamellae.